Enjeux juridiques du contrôle des émissions personnelles de gaz à effet de serre par un dispositif de carte carbone - Sandrine Rousseaux; Nicolas Ochoa; Karine Foucher (Développement Durable et Territoires)
The individual carbon card is an innovative mechanism that helps involve individuals in the fight against climate change. It consists in limiting their greenhouse gas emissions, which requires monitoring a part of their goods and services consumption. This method of personal emissions control is much debated since the carbon card may be perceived as a rationing tool and raises civil liberty issues. Both of these controversial aspects are discussed on the basis of a comparative analysis of how the various carbon card programs, established or contemplated in Europe and in the USA, are designed and implemented. The findings are these controversies are somewhat groundless.